2023
DOI: 10.1186/s42836-023-00195-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning in the prevention of periprosthetic joint infection following total knee arthroplasty: a systematic review

Abstract: Background Machine learning is a promising and powerful technology with increasing use in orthopedics. Periprosthetic joint infection following total knee arthroplasty results in increased morbidity and mortality. This systematic review investigated the use of machine learning in preventing periprosthetic joint infection. Methods A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…Machine learning and artificial intelligence technologies are gradually finding their way into diverse areas. A systematic review with regard to clinical applications of machine learning to PJI prevention revealed its value with respect to preoperative health optimization, surgical planning, early infection diagnosis, early antibiotic use, and prediction of clinical outcomes 61 . Mehta et al 62 compared 14 pathologist-scored histology features and computer vision-quantified cell density (147 patients with osteoarthritis and 60 patients with rheumatoid arthritis) in hematoxylin and eosin-stained images of synovial tissue samples from TKA explants.…”
Section: Machine Learning and Artificial Intelligencementioning
confidence: 99%
“…Machine learning and artificial intelligence technologies are gradually finding their way into diverse areas. A systematic review with regard to clinical applications of machine learning to PJI prevention revealed its value with respect to preoperative health optimization, surgical planning, early infection diagnosis, early antibiotic use, and prediction of clinical outcomes 61 . Mehta et al 62 compared 14 pathologist-scored histology features and computer vision-quantified cell density (147 patients with osteoarthritis and 60 patients with rheumatoid arthritis) in hematoxylin and eosin-stained images of synovial tissue samples from TKA explants.…”
Section: Machine Learning and Artificial Intelligencementioning
confidence: 99%